2021
DOI: 10.28982/josam.935203
|View full text |Cite
|
Sign up to set email alerts
|

Incidental thorax imaging findings in abdominal computed tomography: Results of a tertiary center

Abstract: The study protocol was approved by the Adiyaman Training and Research Hospital Ethics Committee (2020/9-12). All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a study where incidental findings on thorax CT requested for pulmonary thromboembolism were presented, pulmonary nodules and lymphadenopathy were found to be the most common findings [ 36 ]. In another study, which presented incidental pulmonary findings in abdominal CT scans performed for subjects from a similar population as our cohort, atelectatic changes, asbestosis, pleural effusion, and pulmonary nodules were detected [ 28 ]. And, in other studies, pulmonary nodules are the most frequent incidental finding in thorax CT scans [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a study where incidental findings on thorax CT requested for pulmonary thromboembolism were presented, pulmonary nodules and lymphadenopathy were found to be the most common findings [ 36 ]. In another study, which presented incidental pulmonary findings in abdominal CT scans performed for subjects from a similar population as our cohort, atelectatic changes, asbestosis, pleural effusion, and pulmonary nodules were detected [ 28 ]. And, in other studies, pulmonary nodules are the most frequent incidental finding in thorax CT scans [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 90%
“…Here, the frequency of spondylitis was similar in patients with and without apical fibrosis. Although we excluded patients with known or active tuberculosis, as Turkey is an endemic country for tuberculosis, tuberculosis may be the likely cause of the high incidence of apical fibrosis in our cohort; however, in a previous study conducted in the Turkish population, apical fibrosis was not found as an incidental thoracic CT finding [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation